EFFECT OF QUERCETIN ON BLOOD MORPHOLOGICAL COMPOSITION OF WHITE NONBORED RATS - Grigoreva D. A., Leonov V. V., Pavlova O. N., Gulenko O. N. (Science, education, society: trends and prospects, 2020)
Redox processes provide the entire metabolic complex of warm-blooded organisms, while producing a significant amount of free radicals. Free radicals, despite their huge positive role in the body, are capable of forming conditions for the development of various pathogenetic conditions in the event of malfunctioning of the antioxidant defense. The state of homeostasis is indirectly monitored by the hematological characteristics of the blood, which makes it possible to use this aspect to analyze the physiological activity of the body's defense systems. The aim of the study was to study the reactive changes in the morphological composition of rat blood under the influence of quercetin, as a highly effective antioxidant.
Keywords: кровь; эритроциты; лейкоциты; гемоглобин; blood; hemoglobin; лейкоформула; erythrocytes; leukocytes; leukoformula; кверцетин; quercetin